TOOL LIFECYCLE MANAGEMENT IN INDUSTRIAL PRACTICE - Aneta SKOWRON (Management Systems in Production Engineering, 2015)
The paper presents Tool Lifecycle Management (TLM) as an enhancement of traditional approach to the tool manage-ment. The most important assumptions and main research areas of modern tool management are introduced. The au-thor describes functional areas and expectations of TLM. The components and design principles of Industie 4.0 are pre-sented. The main part shows TDM System, developed on the basis of TLM, and an example of its implementation in in-dustrial practice.